1988
DOI: 10.1111/j.1439-0396.1988.tb00049.x
|View full text |Cite
|
Sign up to set email alerts
|

Die Wirkung von Propion‐ und Ameisensäure in der Ferkelaufzucht

Abstract: Zusammenfassung In einem Versuch an Absetzferkeln wurden Zusätze von 0,3 (P 1) und 1,0% Propionsäure (P 2) sowie 0,35 (A 1) und 1,2% Ameisensäure (A 2) vergleichend zu einer Kontrolle (K) mit einem Ferkelaufzuchtfutter ohne Antibiotika bzw. Ergotropika geprüft. In obiger Reihenfolge lagen die Zunahmen bei 246, 313, 349, 312 und 275 g/Tier und Tag. In der Magendigesta waren 28, 30, 16, 8 und 28 mmol organische Säuren/100 g Trockensubstanz enthalten; die Digesta der Grupen P 2, A 1 und A 2 war frei von E.coli. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 11 publications
0
26
1
Order By: Relevance
“…Bolduan et al (1988) reported no effect of FoA supplementation on N-retention and OM and CP (both ileal and faecal) digestibilities (Table 2). However, Eckel et al (1992) reported that FoA supplementation increased the apparent faecal digestibilities of CP and GE by up to 4.4 and 2.5%, respectively (Table 2).…”
Section: Formic Acidmentioning
confidence: 99%
“…Bolduan et al (1988) reported no effect of FoA supplementation on N-retention and OM and CP (both ileal and faecal) digestibilities (Table 2). However, Eckel et al (1992) reported that FoA supplementation increased the apparent faecal digestibilities of CP and GE by up to 4.4 and 2.5%, respectively (Table 2).…”
Section: Formic Acidmentioning
confidence: 99%
“…For formic acid there is some evidence in the literature that it decreases pH and the population density of coliform bacteria in the gastrointestinal tract. Bolduan et al (1988) and Jensen (unpublished) have shown that formic acid reduces the pH in the stomach. Furthermore, Bolduan et al (1988), Kirchgessner et al (1992) and Jensen (unpublished) found that formic acid decreases the population of coliform bacteria in the stomach and small intestine of weaned piglets.…”
Section: Organic Acids (Fermented Feed)mentioning
confidence: 99%
“…Bolduan et al (1988) and Jensen (unpublished) have shown that formic acid reduces the pH in the stomach. Furthermore, Bolduan et al (1988), Kirchgessner et al (1992) and Jensen (unpublished) found that formic acid decreases the population of coliform bacteria in the stomach and small intestine of weaned piglets. However, Gedek et al (1992b) did not find any changes in the population of coliform bacteria in the small intestine when weaned piglets were fed formic acid.…”
Section: Organic Acids (Fermented Feed)mentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors are changes in thermal environment, decreased immune response and changes in diet (Tzipori et al 1980;Barnetr et al 19g9 (Gabert and Sauer 1994). Bolduan et al (1988) observed no effect of formic acid supplementation on nitrogen retention and the apparent ileal and fecal digestibilities of OM and Cp. Howevei, Eckel et al (1992) (Gabert and Sauer 1994).…”
mentioning
confidence: 99%